REGULATORY TRANSFORMATION OF THE DIGITAL ECONOMY AND THE CHALLENGES OF PERSONAL DATA PROTECTION IN INDONESIA: A LITERATURE REVIEW - Zulfikar Yusya Mubarak; Rony Nur Triwibowo (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The transformation of digital economy regulations in Indonesia is a response to the rapid development of information and communication technology that has changed the national economic landscape. The Indonesian government has initiated various policies and regulations to support the growth of the digital economy, including strengthening personal data protection through the Personal Data Protection Law (PDP Law). However, the implementation of these regulations still faces various challenges, such as disharmony between institutions, weak law enforcement, and low digital literacy among the public and business actors. In addition, the rise of personal data leakage cases highlights the importance of monitoring and strengthening cybersecurity infrastructure. This literature review analyses the dynamics of digital economy regulatory transformation and the challenges of personal data protection in Indonesia, and recommends the need for regulatory harmonisation, improved digital literacy, and multi-stakeholder collaboration to create a safe, inclusive, and sustainable digital ecosystem.